Electrocardiographic Analysis of Repolarization Changes in South Indian Children with Kawasaki Disease after the Acute Phase of Illness - Siddhartha Reddy; Maneesh Rai; Ravi Raj Singh Chouhan; Suchetha Rao; Nutan Kamath (International Journal of Pediatrics)
Background. Cardiac involvement in children with Kawasaki disease (KD) may present with repolarization abnormalities which are associated with increased risk of ventricular arrhythmias and sudden cardiac events. Methods. Twenty children with history of KD without cardiac involvement in the acute phase were recruited along with age and sex-matched controls. Twelve-lead ECG was obtained from both groups using CARDIART 610T ECG system at 25 mm/sec and 50 mm/sec paper speed. ECG was repeated in 19 children in the study group after 9±2 months. Measurements (QT dispersion (QTd), T-wave peak to end (Tp-Te) interval, and Tp-Te/QT ratio) were made using standard digital calipers. Statistical analysis was performed with student t-test and analysis of variance (ANOVA) using SSPS version 17.0. Results. The mean value of QTd in the first ECG in cases was significantly high: 43.15±14.13 versus 29.47±8.637 in the controls (p=0.001). The follow-up ECG in 19 cases showed a mean value of 46.26±16.25 versus 43.89+-14.53 at baseline (p=0.440). QTd was increased in the follow-up ECG but was not statistically significant. There was no statistical significance seen in the Tp-Te interval and Tp-Te/Qt ratio as observed in Lead II and Lead V5. Conclusion. Significant increase in the QTd in children with KD indicates repolarization changes in the myocardium even in the absence of clinical carditis. The persistence of this change on follow-up could indicate a possible increased risk for ventricular arrhythmia and warrants long term assessment of the cardiovascular status.